Taxonomical Investigation, Chemical Composition, Traditional Use in Medicine, and Pharmacological Activities of Boswellia sacra Flueck. (18th February 2022) - Miran, Mansour; Amirshahrokhi, Keyvan; Ajanii, Yousef; Zadali, Reza; Rutter, Maxwell W.; Enayati, Ayesheh; Movahedzadeh, Farahnaz
Abstract : Aromatic oleo-gum-resin secreted from B. sacra, reputed as frankincense, is widely used in traditional medicine to treat Alzheimer's disease, gastric disorders, hepatic disorders, etc. Frankincense is also used in the cosmetic, perfume, and beverage and food industries. Frankincense is a rich resource for bioactive compounds, especially boswellic acids and derivatives. Although several reports have described frankincense's constituents and pharmacological activities, there is no comprehensive study that covers the valuable information on this species. Therefore, the current review will focus on the phytochemistry, traditional uses, and pharmacological activities of B. sacra .